Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ptr.7489
|View full text |Cite
|
Sign up to set email alerts
|

Schwarzinicine A inhibits transient receptor potential canonical channels and exhibits overt vasorelaxation effects

Abstract: This study investigated the vasorelaxant effects of schwarzinicine A, an alkaloid recently reported from Ficus schwarzii Koord. Regulation of calcium homeostasis in vascular smooth muscle cells (VSMC) is viewed as one of the main mechanisms for controlling blood pressure. L‐type voltage‐gated calcium channel (VGCC) blockers are commonly used for controlling hypertension. Recently, the transient receptor potential canonical (TRPC) channels were found in blood vessels of different animal species with evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…To gain deeper insights into the potential mode of action of selected schwarzinicine A analogs, we conducted a preliminary MD simulation involving a 44 -bound TRPC complex. In our previous study, we showed that 1 inhibited TRPC3- and TRPC6-mediated calcium entry into cells . Due to the absence of an inhibitor-bound TRPC3, we chose to pursue our computational investigation based on a closed conformation of the antagonist AM-1473-bound TRPC6 structure, previously resolved through cryo-EM (PDB ID: 6UZA).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To gain deeper insights into the potential mode of action of selected schwarzinicine A analogs, we conducted a preliminary MD simulation involving a 44 -bound TRPC complex. In our previous study, we showed that 1 inhibited TRPC3- and TRPC6-mediated calcium entry into cells . Due to the absence of an inhibitor-bound TRPC3, we chose to pursue our computational investigation based on a closed conformation of the antagonist AM-1473-bound TRPC6 structure, previously resolved through cryo-EM (PDB ID: 6UZA).…”
Section: Resultsmentioning
confidence: 99%
“…Following method A, compound 7 was prepared from 64b and propylamine in 49% yield (light yellow oil): 1 N-Phenethyl-1-phenylpentan-3-amine (8). Following method A, compound 8 was prepared from 64e and phenethylamine in 72% yield (yellow oil): 1 N-Phenethyl-1-phenylpentan-2-amine (9). Following method A, compound 9 was prepared from 64c and phenethylamine in 26% yield (yellow oil): 1 28).…”
Section: -(4-cyanophenyl)-n-methoxy-n-methylpropanamide (63o)mentioning
confidence: 99%
See 3 more Smart Citations